The Problem of Young Families’ Housing and Labour Force Movement - Jurevičienė, Daiva (Ekonomika, 2007)
House is one of the main factors that influence the choice of the living place. A comparison of housing structures in various countries has shown that households own the main share of houses in Lithuania, while social housing supply has nearly disappeared. The increasing building facilities of houses do not satisfy the growing needs. The demand of houses is influenced also by softer credit requirements of banks. There have been various housing financing programs supported by the state since the declaration of Independence in Lithuania, which in one or another way are tuned to youth, but when the state established limitations for the amount of owned assets and incomes, the support of state has become ineffective during the latest growth of prices in the housing sector. Analysis of the previous and existing programs that are turned to the youths’ house purchase, information of the Department of Statistics on the persons that took advantage of the state support for house purchase and the data on the persons that took advantage of the tax privilege for the - interest for mortgage loans are presented in the article. Conclusions on the existing flaws of the Lithuanian housing market structure and suggestions that could be useful for the improvement of the living conditions of youth and support the consolidation of the labour market in Lithuania are presented.